Exploring of Minangkabau Local Knowledge Management in Agam District, Indonesia: A Preliminary Study - Elva Rahmah; Shamila Mohamed Shuhidan; Wan Aida Wan Yahaya (International Journal of Environment, Architecture, and Societies, 2023)
Local knowledge is the knowledge found in local communities that consists of a set of experiences that have been accumulated and provides information that shows the local community or local culture’s behavioral characteristics. As a result of a variety of factors, such information is at risk of being obliterated, including lack of interest from younger generations and low life expectancy, where knowledge enables individuals to die before passing it to the next generation. Therefore, this paper aims to look at the perspective of community leaders on the status of local knowledge. The data collection method used in this research is an interview. The results of this study indicate that the Minangkabau community in Agam Regency, Indonesia recognises their customs, cultures, and habits that are different from the general public. The investigation was carried out by involving community leaders related to the dimensions of local knowledge: (1) The environmental dimension of local knowledge through Lubuak Larangan is a type of community custom and culture that involves the preservation of river and lake areas within specific territorial borders and rules; (2) dimensions of local values; (3) dimensions of local abilities are employed to ensure survival by farming, livestock or industry; (4) dimensions of local resources: utilization of natural resources. The Minangkabau community divided its forest into two categories: prohibited forest and forest cultivated or utilised for economic interests and family needs; (5)  the local decision-making mechanism’s dimensions; and (6) local group solidarity dimensions: religious rituals, traditional ceremonies, arts, and cooperation.